Combined effects of meal frequency and exercise on postprandial lipaemia - Mok, Alexander (2014)
PURPOSE: This study examined 1-large or 2-smaller isocaloric meals, with and without exercise on postprandial lipaemia (PPL), a major risk factor for cardiovascular disease. These findings can contribute to public health recommendations.